Wench [large type] : a novel - Perkins-Valdez, Dolen (Thorndike Press, 2010)
Tawawa House in many respects is like any other American resort before the Civil War. Situated in Ohio, the idyllic retreat suits the needs of the Southern white men who vacation there every summer with their slave mistresses. Lizzie, Reenie, and Sweet have become friends over the years and share developments in their own lives. They don't bother with questions of freedom, though - until truth-telling Mawu comes to the resort.